PARTISIPASI ORANG MUDA KATOLIK DALAM LITURGI DI PAROKI SANTO YUSUP BATURETNO WONOGIRI JAWA TENGAH - Maria Goretti Utami; Antonius Tse (Bahasa Indonesia, 2019)
In the present, there is a phenomenon that the catholic young no longer interested to the activities in the church, especially liturgcal activities. The participation of young peoples in the liturgy of the Catholic Church is very low. For example, in a Sunday Mass, there are very few young peoples participating in the Church. However, most ofthose participating in the Sunday mass are the old people. Based on the reality of youth involvement in the liturgy, the researcher of wanted to explore the extent to which the young people participating in the liturgy of the Catholic Church. In the study, researcher used qualitative approach. Data were collected through interviews. Results of the study revealed that very few young people involved in the liturgical activities. However, only few respondents involved the liturgical activities as altar boys, lectors, chairs and so on. There are some reasons that made the young catholics did not involve, and in the liturgical activities such as laziness and many other activities they involved. There are some action that could be taken to encourage the young people to involve in the liturgycal activities such as to give them more motivation and encouragement to be involved more in the liturgical activites.